Dashboard Sistem Informasi Penjualan Obat (Studi Kasus Apotek RSUD Prabumulih) - Dede Renza Apriliandi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
RSUD Prabumulih is an institution that is engaged in the health sector with many business scopes, one of which is a pharmacy RSUD Prabumulih manages large amounts of transaction data reaching tens of thousands of data within three years. In its operational activities, RSUD Prabumulih uses the MyHospital application to manage drug purchase and sale transaction data. However RSUD Prabumulih does not yet have a dashboard application for monitoring its business process activities. Therefore, it is necessary to develop Business Intelligence to manage drug sales data and then create a data visualization in the form of a dashboard. The method used is to apply the BI roadmap method. The ETL process for designing the data warehouse is done using Pentaho Data Integration (PDI), while the dashboard visualization is done using the Tableu application. . The results of the application of the Tableu application are in the form of a data visualization dashboard that produces the information needed by RSUD Prabumulih to assist the leadership of a company or agency in making decisions. Keywords— Business intelligence, Dashboard, RSUD, Tableu